Issues on designing server squads for future large-scale distributed and parallel computing systems - Yang, C.-Q.; Ali, M.S. (Future Trends of Distributed Computing Systems, 2nd IEEE Workshop, 1990)
The authors address some of the important issues concerning the construction of server squads in massively parallel and distributed systems. Constructing a system with thousands of processors has become a real possibility in recent years. A server squad is a group of server processes that cooperatively provides services in such systems. Such server squads are necessary in order to avoid possible congestion of services among clients as systems become larger. Issues discussed include the configuration of a server squad, which defines the way individual server processes cooperate with each other; the effects of squad structures on the communication pattern; the relationship between neighboring members of the squad; and information sharing within a squad. Some general rules for the placement of individual servers in a system and the partitioning of clients among members of a squad, and the mechanisms and policies for adaptive growth of a server squad are also discussed.< >